2017
DOI: 10.1097/dad.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial Melanoma in the Stomach After Treatment With Immune Checkpoint Blockade Therapy

Abstract: Melanoma is the most common tumor to metastasize to the gastrointestinal tract, commonly affecting the small intestine, colon, and anorectum. Primary mucosal melanoma can arise in any gastrointestinal site, most frequently affecting anorectal mucosa. Melanoma involving the gastric mucosa, specifically, is exceedingly rare and carries a poor prognosis with a median survival of 5 months. The presence of atypical melanocytes exclusively within gastric epithelium has not been previously described. We report a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In review of the published literature using the terms conjunctiva, melanoma, BRAF, KIT, pembrolizumab, ipilimumab, interferon and genetics, we found a 2016 study on the efficacy of anti-PD-1 agents in acral and mucosal melanomas supported its use in clinical practice [21, 22]. In contrast, a 2017 study concluded that checkpoint inhibition for advanced mucosal melanoma revealed no clinical response and disease progression [23].…”
Section: Discussionmentioning
confidence: 99%
“…In review of the published literature using the terms conjunctiva, melanoma, BRAF, KIT, pembrolizumab, ipilimumab, interferon and genetics, we found a 2016 study on the efficacy of anti-PD-1 agents in acral and mucosal melanomas supported its use in clinical practice [21, 22]. In contrast, a 2017 study concluded that checkpoint inhibition for advanced mucosal melanoma revealed no clinical response and disease progression [23].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the third case of melanoma with gastric involvement treated with BRAF inhibitors. 24 , 29 BRAF is one of the most significant gene mutations in cutaneous melanoma (approximately 50%) but is rare in mucosal forms of the disease. 30 The presence of skin lesions and substantial disease burden in a case of poorly differentiated gastric cancer must raise the suspicion of an incorrect histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is the most common tumor to metastasize to the gastrointestinal tract, commonly affecting the small intestine, colon, and anorectum. 3,4 Melanoma involving the stomach is extremely rare, and the prognosis is generally poor. 5 In this case, the patient had a primary lesion in the occipital skin, progressed without sentinel lymph node metastasis but displayed mucosal lentiginous metastases in the stomach.…”
mentioning
confidence: 99%
“…Further pathological biopsy of gastric cardia, fundus, and body tissue identified as metastases of melanoma ( B ). Melanoma is the most common tumor to metastasize to the gastrointestinal tract, commonly affecting the small intestine, colon, and anorectum 3,4 . Melanoma involving the stomach is extremely rare, and the prognosis is generally poor 5 .…”
mentioning
confidence: 99%